Static Analysis of a Laminated Rubber-Metal Spring Using Finite Element Method - Putra, Azma; Norfarizan, Siti; Samekto, H; Salim, Mohd Azli (Trans Tech Publications, 2014)
The laminated rubber-metal spring has been widely applied for earthquake vibration isolation which deals mainly for horizontal motion at a very low frequency input. This article presents the effect of a vertical vibration input, which is also aimed at applying the laminated spring for high frequency excitation. Static analysis is discussed here using the Finite Element Analysis (FEA) to observe the stress and strain distribution as well as the safety factor of the isolator due to the axial force. Solid rubber spring experienced greater deformation while it decreased for the laminated rubber-metal spring as more plates were embedded in the rubber. However, higher stress distributions occurred on spring with multiple plates compared to solid rubber and the stress concentrate on steel plate layers. Strain distribution was observed to be high at solid rubber spring and it was decreasing on the laminated rubber-metal spring. The critical part for the strain distribution in the laminated rubber-metal spring was in the rubber layers.